2010
DOI: 10.1172/jci39678
|View full text |Cite
|
Sign up to set email alerts
|

Wolfram syndrome 1 gene negatively regulates ER stress signaling in rodent and human cells

Abstract: Wolfram syndrome is an autosomal-recessive disorder characterized by insulin-dependent diabetes mellitus, caused by nonautoimmune loss of β cells, and neurological dysfunctions. We have previously shown that mutations in the Wolfram syndrome 1 (WFS1) gene cause Wolfram syndrome and that WFS1 has a protective function against ER stress. However, it remained to be determined how WFS1 mitigates ER stress. Here we have shown in rodent and human cell lines that WFS1 negatively regulates a key transcription factor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
343
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 350 publications
(359 citation statements)
references
References 47 publications
12
343
3
1
Order By: Relevance
“…It has been shown that WFS1-deficient pancreatic β cells have high baseline ER stress levels and impaired insulin synthesis and secretion. Thus, WFS1-deficient β cells are susceptible to ER stress mediated cell death (5,6,32,(40)(41)(42). The functions of WFS2 are still not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that WFS1-deficient pancreatic β cells have high baseline ER stress levels and impaired insulin synthesis and secretion. Thus, WFS1-deficient β cells are susceptible to ER stress mediated cell death (5,6,32,(40)(41)(42). The functions of WFS2 are still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…It follows that genetic or acquired ER dysfunction can trigger a variety of common diseases, including neurodegenerative diseases, metabolic disorders, and inflammatory bowel disease (3,4). Breakdown in ER function is also associated with genetic disorders such as Wolfram syndrome (5)(6)(7)(8). It is challenging to determine the exact effects of ER dysfunction on the fate of affected cells in common diseases with polygenic and multifactorial etiologies.…”
mentioning
confidence: 99%
“…other chaperones) release the sensors for further activation upon additional EnR stress (reviewed in Ma & Hendershot [30]). While numerous chaperones are likely to play a role in sensor inhibition, such as BI-1 [31,32], AIP1 [33] and RACK1 [34] for IRE1, and WFS1 [35] for ATF6, for simplicity of the model, we lump the effects of these other chaperones into the effect of a single chaperone, GRP94. While not redundant to GRP78, GRP94 plays an important role in EnR stress control [36][37][38].…”
Section: Unfolded Protein Response Modulementioning
confidence: 99%
“…22 Mutations in WFS1 are deleterious for protein expression. 23,24 WFS1 depletion in cells induces high levels of endoplasmic reticulum stress, activating the unfolded protein response, 25,26 and affects insulin processing and secretion. 27,28 Glycosylation sites were identified as important for protein stability, 22 and a region that targets unfolded WFS1 to degradation (degron) has been identified.…”
mentioning
confidence: 99%